Oncolytic Activity of Bacteria used in Cancerous Disease Gene Therapy (Global Journal of Medical Research, 2016)
Gene therapy is a therapeutic strategy based on using genes as pharmaceuticals. Gene therapy holds promise for treating a wide range of diseases, including cancer, cystic fibrosis, heart disease, diabetes, hemophilia and AIDS. Various types of genetic material are used in gene therapy; double-strained DNA (dsDNA), single strained DNA (ssDNA), plasmid DNA and antisense oligodeoxynucleotides (ASON), adenoviruses, retroviruses, undeveloped/ plasmid DNA and bacteria. The use of bacteria in cancer therapy can be advantageous for various reasons compared to classic chemotherapy or other microorganisms. Bacteria can adhere and invade tumor cells, and they are capable of proliferation and of establishing extracellular colonies. Other than that, their genome length enables them to be recipient to a quantum of exogenous therapeutic genes (for example, enzymes activating precursors and cytokines). The most important thing from the clinical safety view is they can be killed by antibiotics (such as metronidazole) if complications in further treatment arise. For comparison, the capacity of viral vectors is limited and in case of side effects viruses cannot be eliminated by antibiotics.
Keywords: gene therapy; salmonella spp; clostridium spp; therapeutic strategy